Parental stress and dyadic adjustment among parents of children with ASD: Moderating effects of dyadic coping and perceived social support. (April 2022) - Fallahchai, Reza; Fallahi, Maryam
Highlights: Child Behavior Problems influenced the stress of parents of children with ASD. The stress of raising a child with ASD influenced the dyadic adjustment of parents. Dyadic coping can play an important role in managing stress among parents of children with ASD. Perceived social support can moderate the effect of stress on the parents' dyadic adjustment. A relatively large number of fathers of children with ASD participated in this study. Abstract: Background: Previous studies examining the association between child behavior problems and parental stress have reported mixed results. Aim: This study aimed to explore the associations between child behavior problems and parental stress as well as parental stress and dyadic adjustment, and the moderating roles of stress communication, perceived partner supportive dyadic coping, and perceived social support in the relationship between parental stress and dyadic adjustment. Methods and procedures: Data were derived from 233 parents with at least one child with ASD from Iran. Outcomes and results: The results demonstrated that child behavior problems were positively associated with parental stress whereas parental stress was negatively associated with dyadic adjustment. Furthermore, stress communication, perceived partner supportive dyadic coping, and perceived social support moderated the relationship between parental stress and dyadic adjustment. Conclusions: The current findings may attract the attention of clinicians and professionals who work with parents of children with ASD on the effect of stress and how to manage stress on these parents' dyadic adjustment.